Developing TAMEx Model For Availability Aspect of E-Exam Security in WLAN Environment - Sukadarmika, Gede; Sari Hartati, Rukmi; ., Linawati; Sastra, Nyoman Putra; Amrita, A.A.N. (International Journal of Engineering and Emerging Technology; Vol 5 No 1 (2020): January - June, 2020)
The internet has provided tremendous impact in educational development throughout the world. E-Exam system is one of educational component which has been used increasing dramatically for evaluating educational process. As an e-exam feature, uniformity of system access and time duration of the exam to all examinees is very important to be considered. Exam manager usually utilizes a fixed network to connect all e-exam terminal in order to maintain service stability on e-exam systems. However, the use of a fixed network will be difficult to be implemented if the number of examines is large. There are not many Education institutions have adequate ICT infrastructure or e-exam terminals for all students. Most institutions develop WLAN networks as an alternative to being able to provide ICT services to all students. With the development of mobile device technology (Handphone or Laptop) that strongly supports the learning process through mobile devices. This research aims to develop application of the Time Adaptive for Mobile E-Exam (TAMEx) Model. It serves to maintain the reliability of e-exam implementation on WLAN networks. The possible connection disruptions is anticipate by seeking time compensation only to participants who has experienced the connection problem. The time compensation must be accordance to the duration of the occurrence of connection loss. Application development has been carried out and is functioning properly. The report of application shows that it has succeeded in identifying the connection disturbance duration and provide time compensation to the proper examinee.